Deficiencia normativa en los contratos de obra realizados por el estado, en lo referente a la garantía de los diez años subsiguientes a la entrega definitiva de la obra, respecto de los vicios de construcción o de suelo, que el contratista o sus empleados debían conocer en razón de su trabajo. - Jara Viñan, Lenin Santiago (2022)
The objective of this research is to carry out an analysis of the characteristics of the provisions contained in the work contracts to be signed by the State and the successful bidder, to determine if there is a regulatory deficiency in the work award contracts, with respect to the guarantees subsequent to delivery and final reception of the work. Determining requirements are the effects produced by the normative deficiency in the construction contracts carried out by the State, with respect to the construction or soil vices that the contractor or employees harm from knowing due to their work. Determine if there is a need to reform the Organic Law of Public Procurement or its Regulations, regarding the guarantees that may exist in the work contracts after the final delivery and reception of the same. For the realization of some objectives, a doctrinal, conceptual and legal study was carried out, the methodology was based on various study methods such as scientific, inductive, deductive, analytical, exegetical, hermeneutical, comparative and statistical. The methodological techniques applied were, in the first instance, the documentary collection technique, where from the theoretical framework important themes are externalized in order to have correct foundations about the research topic, techniques such as the interview with legal professionals and the survey to the students of the University, this, with the purpose of knowing their position and opinion regarding the subject of study. As one of the main results, 73.3% had knowledge of what a construction defect, soil defect or material defect is, as well as 66.7% agree that public resources do not they are adequately covered by Ecuadorian legislation under the Civil Code and the Organic Law of the National Public Procurement System. On the other hand, cases such as the Coca Codo Sinclair hydroelectric plant and the Esmeraldas Refinery are also analyzed, which until now are national news due to the vices found in their constructions. That is why it is proposed to make a reform to the Organic Law of the National System of Public Procurement of Ecuador, specifically to article 74 and that it is also considered a section for hidden construction defects. The relevance of this reform proposal is due to the well-known cases of corruption that have occurred in public procurement processes, always bearing in mind that public finances must be conducted in a sustainable, responsible and transparent manner, seeking the economic stability of Ecuadorians.